Corporate governance and intellectual capital disclosure practices in sri lankan non-financial institutions - Jeyan Suganya, D.F. (University of Jaffna, 2021)
This study examines the impact of corporate governance practices on intellectual capital disclosure in Sri Lankan non-financial institutions. Independent variables of the study comprise various forms of corporate governance attributes such as board size, CEO duality, audit committee size, and board independence. Intellectual capital disclosure is measured using a disclosure index which includes human, relational and structural intellectual capital disclosures. Data were collected from the annual reports of 45 non-financial institutions listed in the Colombo Stock Exchange from 2015 to 2019. Descriptive statistics, correlation analysis, and multiple regression analysis were performed to analyze the data. Out of four variables tested, only audit committee size and board independence had a significant impact on intellectual capital disclosure. Audit committee size had a significant positive impact on intellectual capital disclosure, while board independence had a significant negative impact on intellectual capital disclosure. It reveals that corporate governance practices improve disclosures of intellectual capital in Sri Lanka. It will resolve problems with information asymmetry among investors. The findings underscore the importance of creating appropriate policies and regulations relating to corporate governance.
Keywords: Corporate governance; Intellectual capital disclosure; Human capital; Structural capital; Non-financial firms